John Rawls’s Concept of Justice as Fairness - Edor J. Edor (PINISI Discretion Review, 2021)
John Rawls's theory of Justice is one of the most influential conceptions of justice. Scholars have continued to study it to understand the principles in the formation and to further frame it in the context of contemporary situations. This paper contributes to the ongoing discussion by presenting Rawls’ concept of “justice as fairness” as it evolved from the traditional conception of justice to the modern-shift in the concept. The paper also examines Rawls’s concept of justice as fairness, and it focuses on analyzing or studying the concept of justice as fairness in terms of the principles used in its formulations. Several criticisms developed by political philosophers to critique the idea were examined. In conclusion, it was argued that Rawls's invention of the veil-of-ignorance for the original position has affected the theory negatively.